Change of body composition in process of power conditional training - D.M. Anikieiev (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to work out recommendations on choosing of exercises for power conditional trainees, considering decrease of fat mass percentage as the purpose. Methods: analysis of changes of body composition of trainees, practicing different kinds of conditional power training. Results: the data about influence of different physical loads on thickness of subcutaneous fat in different parts of body have been generalized. Recommendations on choosing of exercises for power conditional trainees for body composition improving have been presented. It was found that fat loss occurs quicker in upper part of body (subcutaneous and visceral). This is observed with increasing of motor functioning and reducing calories of eating. When training any separate muscular group changes of subcutaneous fat take place not compulsory in body parts, in which the trained group is located. Conclusions: it is purposeful to mainly use basic (multi-joint) exercises in power conditional training.